The Product Range Conceptualization For Islamic SME Financing - Ahmad Aizuddin Hamzah; Norhazlina Ibrahim; Amir Shaharuddin; Sumaiyah Abd Aziz; Haneffa Muchlis Gazali (Labuan Faculty of International Finance, Universiti Malaysia Sabah, 2024)
Non-Indexed Publication